Aphasia education: speech-language pathologists' perspectives regarding current and optimal practice. Issue 8 (3rd August 2018) - Rose, Tanya A.; Balse, Anita; Osmond, Sarah; Poon, Angela; Simons, Natasha; Wallace, Sarah J.
ABSTRACT: Background : People with aphasia (PWA) and their families (PWA-F) have conveyed that the receipt of information and education is a key component of rehabilitation which supports access to services and participation in healthcare decision-making. Best practice recommendations state that education about aphasia should be tailored, aphasia-friendly, and provided on multiple occasions and in a variety of formats. To date, there has been little research examining the current practices of speech-language pathologists (SLPs) in the provision of education or their perspectives on barriers and facilitators to achieving optimal aphasia education practices. Aims : The aim of this study was to explore current and optimal aphasia education practices from the perspective of Australian SLPs. Methods and Procedures : This study used a cross-sectional survey design, comprising both quantitative and qualitative questions. An online survey was distributed to Australian SLPs via professional networks. Quantitative data were analysed using descriptive statistics and qualitative data using content analysis. Outcomes and Results : This study reports data from 130 Australian SLPs. The majority of SLPs (>70%) reported that they provided information to both PWA and PWA-F about (1) the definition of aphasia, (2) characteristics of aphasia, (3) causes of aphasia, (4) aphasia recovery, (5) strategies to assist communication, and (6) coping strategies. However, the majority of SLPs reported that they did not provide information to friends on any of the presented topics. Many SLPs (>95%) provided both face-to-face and written aphasia information, and approximately half (55%) provided aphasia education that could be accessed via the Internet. All but one SLP reported using pre-prepared written information and less than half (45%) considered those materials to be formatted in an aphasia-friendly way. The majority of SLPs (65%) reported that they did not have a systematic approach to providing aphasia education, they (82%) did not evaluate the effectiveness of aphasia education, and they (92%) did not provide optimal aphasia education. SLPs reported that greater access to aphasia-friendly formatted information (94%) and written information for family members (92%) would assist in optimising aphasia education. Furthermore, 82% of SLPs indicated that they would support an Australia-wide move to use the term aphasia, rather than dysphasia . Conclusions : The majority of SLPs reported providing information to PWA and PWA-F in a variety of formats; however, information provision did not commonly extend to friends. Increased tailoring of information and access to aphasia-friendly information would assist SLPs in meeting best practice recommendations for aphasia education.